(untitled) (Journal of Bio-Science, 2026)
Understanding the bacteria found in fishponds is essential for fish health management and disease prevention, especially given the increasing public health risks associated with antibiotic resistance in aquatic ecosystems. In this study, the multidrug resistance profile of bacteria in fishpond water was examined, and identification of bacteria was conducted using 16S rRNA sequencing method. The study revealed a worrying trend of antibiotic resistance in bacteria isolated from various fishponds in Rajshahi District, Bangladesh. All the antibiotics tested showed significant resistance, with sulfadiazine-trimethoprim being the highest (86.61%) and ciprofloxacin the lowest (49.187%). Alarmingly, nearly 38.09% of the bacteria were resistant to all the antibiotics tested. The present study identified a diverse bacterial community composed of 37 distinct bacterial strains belonging to 16 different genera. Enterobacter emerged as the most abundant genus, followed by Klebsiella, Bacillus, Escherichia, Acinetobacter, Shigella and among others. These dominant bacteria genera also demonstrated a high degree of resistance to the antibiotics tested in this study. In addition, the majority of the bacterial isolates identified are known to be pathogenic. The increase in multidrug-resistant bacteria (MRB) in fishponds poses a significant threat to aquatic organisms and human health, as infections can spread through contaminated fish or through direct contact with pond water. This emphasizes the need for judicious use of antibiotics in aquaculture to limit resistance development and its transmission through the food chain. J. Bio-Sci. 33(1): 67-78, 2025